Lnc'ing Ca2+, SERCA and cardiac disease. (June 2018) - Vervliet, Tim; Robinson, Emma L.; Roderick, H. Llewelyn
Highlights: Decreased SR Ca 2+ and SERCA activity contribute to cardiac dysfunction in disease. The ZFAS1 long non-coding RNA is upregulated in cardiac disease. ZFAS1 is reported to directly inhibit SERCA activity. By homology with SERCA2a, ZFAS1 may also regulate the ubiquitous SERCA2b isoform. Potential ZFAS1 roles in pathologies involving dysregulated ER Ca 2+ are discussed. Abstract: Loss of SERCA function contributes to reduced contractility, Ca 2+ overload and arrhythmias in the diseased heart. A long non-coding RNA ( ZFAS1 ) upregulated in cardiac disease is reported to directly inhibit SERCA function. The implications for cardiac disease and the wider roles of SERCA are discussed.